Foreign trade and economic growth: An analysis of the impact of development (International Seven Journal of Multidisciplinary, 2023)
International trade plays a central role in the economic growth prospects of countries. The advantages of international trade are linked to the specialization in the production of goods and services in which a country has a comparative advantage, allowing for a more efficient allocation of resources and increased productivity. However, the impact of trade on the economy goes beyond theoretical benefits. Empirical studies have examined the impact of trade policies, such as trade liberalization, in developing economies. Many of these studies have emphasized the importance of each country's specific characteristics, such as income elasticity of imports and the institutional environment, in determining the effects of trade on economic growth. The Keynesian theory of international trade also emphasizes the relevance of effective demand and the balance of payments in long-term economic growth. It argues that government demand management policies play a crucial role in promoting economic growth, while balance of payments constraints can be significant obstacles. In summary, the study of the relationship between international trade and economic growth is multifaceted and complex, involving an analysis of classical and contemporary economic theories, as well as the implications of international trade policies and the institutional environment. This article aims to contribute to a deeper understanding of this fundamental interaction for economic development.